Health, Homelessness Severity, and Substance Use among Sexual Minority Youth Experiencing Homelessness: A Comparison of Bisexual Versus Gay and Lesbian Youth. Issue 7 (1st September 2020) - Siconolfi, Daniel; Tucker, Joan S.; Shadel, William G.; Seelam, Rachana; Golinelli, Daniela
ABSTRACT: Lesbian, gay, bisexual, and questioning (LGBQ) youth are overrepresented among youth experiencing homelessness (YEH), and health disparities among LGBQ youth are well-documented. LGBQ youth are typically aggregated as a single sexual minority group; however, research suggests that bisexual youth may have greater mental health, substance use, and physical health risks relative to their gay and lesbian peers. In a probability sample of LGBQ YEH in Los Angeles County (n = 183), we examined subgroup differences in homelessness severity, depression, physical health, and substance use, focusing on differences between bisexual and gay/lesbian youth due to the small subsample of questioning youth. Indicators of homelessness severity were standalone outcomes, and also were integrated as control variables with gender, age, race/ethnicity, and education in multivariable models. Bisexual youth were more likely to have become unaccompanied homeless persons as minors (OR = 4.35, 95% CI 1.85–10.23), and to have not recently utilized emergency shelters or transitional housing at least once in the past month (OR = 6.41; 95% CI 2.41–17.03). Bisexual youth were more likely to have probable depression (OR = 4.06, 95% CI 1.41–11.68). Among sexual minority YEH, bisexual youth may be at elevated risk for depression, in addition to more severe homelessness.